2007
DOI: 10.1186/1476-069x-6-10
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying geocode location error using GIS methods

Abstract: Background: The Metropolitan Atlanta Congenital Defects Program (MACDP) collects maternal address information at the time of delivery for infants and fetuses with birth defects. These addresses have been geocoded by two independent agencies: (1) the Georgia Division of Public Health Office of Health Information and Policy (OHIP) and (2) a commercial vendor. Geographic information system (GIS) methods were used to quantify uncertainty in the two sets of geocodes using orthoimagery and tax parcel datasets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 21 publications
3
49
0
1
Order By: Relevance
“…Positional error ranged from negligible (5 meters Euclidean distance) to exceptional (almost 20,000 meters, in the case of a golf course) and was larger than distances observed in residential address geocoding validation studies (11)(12)(13)(14)(15). However, this study examined physical activity facilities, which are often large in size and could have ambiguous point locations (e.g., golf courses, which cover a relatively large geographic area), rather than residences.…”
Section: Positional Accuracymentioning
confidence: 91%
See 1 more Smart Citation
“…Positional error ranged from negligible (5 meters Euclidean distance) to exceptional (almost 20,000 meters, in the case of a golf course) and was larger than distances observed in residential address geocoding validation studies (11)(12)(13)(14)(15). However, this study examined physical activity facilities, which are often large in size and could have ambiguous point locations (e.g., golf courses, which cover a relatively large geographic area), rather than residences.…”
Section: Positional Accuracymentioning
confidence: 91%
“…Despite the recognition of these potential errors and considerable growth in the use of GIS technology in health research, existing validation studies generally focus on the positional error of geocoded residential addresses (11)(12)(13)(14)(15)(16). Count and attribute error in databases of community resources, as opposed to residential addresses that are managed in GIS programs have not been assessed.…”
Section: Introductionmentioning
confidence: 99%
“…meters, and larger in rural areas than in urban areas (Bonner et al 2003;Cayo and Talbot 2003;Morton et al 2007;Schootman et al 2007;Strickland et al 2007;Ward et al 2005;Whitsel et al 2004;Whitsel et al, 2006). Coordinates assigned by street-level geocoding are more likely to be close to their true location than those assigned by postal geocoding.…”
Section: This Coordinate Assignment Methods Is Called Street-level Geomentioning
confidence: 99%
“…Ideally, this process places addresses into the block where they really are. Investigations of the accuracy of assignment to census geographies have reported that 35% of addresses are placed in the wrong blocks, and five percent in the wrong tract (Krieger et al 2001;Morton et al 2007;Ratcliffe 2001;Schootman et al 2007;Strickland et al 2007). …”
Section: This Coordinate Assignment Methods Is Called Street-level Geomentioning
confidence: 99%
“…An issue being recognized more currently is that of geocoding accuracy. Zandbergen (2007) found a median street coding error of 41 m, with a 99th percentile error of 273 m; Schootman et al (2007) report errors of 51 m or more; Strickland et al (2007) report errors ''less than 100 m''; and Zimmerman et al (2007) report a median error of 44 m. These findings shed doubt on epidemiological findings based on residential proximity to busy streets of the order of 50 m, as discussed above, especially given the exponential nature of concentration decay downwind of busy roads. It seems likely that more reliable results might be obtained using continuous rather than categorical measures of residential proximity, such as in Tonne et al (2007).…”
Section: Problems Of Confounding Collinearity and Measurement Errormentioning
confidence: 99%